Transcranial Magnetic Stimulation for Post-traumatic Stress Disorder - Edinoff, Amber N.; Hegefeld, Tanner L.; Petersen, Murray; Patterson, James C.; Yossi, Christopher; Slizewski, Jacob; Osumi, Ashley; Cornett, Elyse M.; Kaye, Adam; Kaye, Jessica S.; Javalkar, Vijayakumar; Viswanath, Omar; et al. (Frontiers in Psychiatry, 2022)
Post-traumatic stress disorder (PTSD) is a psychiatric disorder that causes significant functional impairment and is related to altered stress response and reinforced learned fear behavior. PTSD has been found to impact three functional networks in the brain: default mode, executive control, and salience. The executive control network includes the dorsolateral prefrontal cortex (DLPFC) and lateral PPC. The salience network involves the anterior cingulate cortex, anterior insula, and amygdala. This latter network has been found to have increased functional connectivity in PTSD. Transcranial Magnetic Stimulation (TMS) is a technique used in treating PTSD and involves stimulating specific portions of the brain through electromagnetic induction. Currently, high-frequency TMS applied to the left dorsolateral prefrontal cortex (DLPFC) is approved for use in treating major depressive disorder (MDD) in patients who have failed at least one medication trial. In current studies, high-frequency stimulation has been shown to be more effective in PTSD rating scales posttreatment than low-frequency stimulation. The most common side effect is headache and scalp pain treated by mild analgesics. Seizures are a rare side effect and are usually due to predisposing factors. Studies have been done to assess the overall efficacy of TMS. However, results have been conflicting, and sample sizes were small. More research should be done with larger sample sizes to test the efficacy of TMS in the treatment of PTSD. Overall, TMS is a relatively safe treatment. Currently, the only FDA- approved to treat refractory depression, but with the potential to treat many other conditions.